DNA‐based probes for flow cytometry analysis of endocytosis and recycling. (7th February 2017) - Dumont, Claire; Czuba, Ewa; Chen, Moore; Villadangos, Jose A.; Johnston, Angus P.R.; Mintern, Justine D.
Abstract : The internalization of proteins plays a key role in cell development, cell signaling and immunity. We have previously developed a specific hybridization internalization probe (SHIP) to quantitate the internalization of proteins and particles into cells. Herein, we extend the utility of SHIP to examine both the endocytosis and recycling of surface receptors using flow cytometry. SHIP was used to monitor endocytosis of membrane‐bound transferrin receptor (TFR) and its soluble ligand transferrin (TF). SHIP enabled measurements of the proportion of surface molecules internalized, the internalization kinetics and the proportion and rate of internalized molecules that recycle to the cell surface with time. Using this method, we have demonstrated the internalization and recycling of holo‐TF and an antibody against the TFR behave differently. This assay therefore highlights the implications of receptor internalization and recycling, where the internalization of the receptor‐antibody complex behaves differently to the receptor‐ligand complex. In addition, we observe distinct internalization patterns for these molecules expressed by different subpopulations of primary cells. SHIP provides a convenient and high throughput technique for analysis of trafficking parameters for both cell surface receptors and their ligands. Abstract : We demonstrate the utility of a DNA‐based specific hybridization internalization probe (SHIP) assay to examine endocytosis and recycling of ligands that bind to receptor proteins using flow cytometry. We monitored endocytosis of membrane‐bound transferrin receptor (TFR) and its soluble ligand transferrin (TF) in cell lines and primary cells. We demonstrate that internalization and recycling of holo‐TF, and an antibody against the TFR behave differently. SHIP provides a convenient and high‐throughput technique for analysis of trafficking of cell surface receptors and ligands.